Scientific misbehavior in economics - Necker, Sarah (Research Policy, 2014)
This study reports the results of a survey of professional, mostly academic economists about their research norms and scientific misbehavior. Behavior such as data fabrication or plagiarism are (almost) unanimously rejected and admitted by less than 4% of participants. Research practices that are often considered "questionable," e.g., strategic behavior while analyzing results or in the publication process, are rejected by at least 60%. Despite their low justifiability, these behaviors are widespread. Ninety-four percent report having engaged in at least one unaccepted research practice. Surveyed economists perceive strong pressure to publish. The level of justifiability assigned to different misdemeanors does not increase with the perception of pressure. However, perceived pressure is found to be positively related to the admission of being involved in several unaccepted research practices. Although the results cannot prove causality, they are consistent with the notion that the "publish or perish" culture motivates researchers to violate research norms.
CRIS-Team Scopus Importer:2022-05-03
Keywords: "publish or perish"; Academic labor market; Economics of crime; Scientific misbehavior; Social norms